Enhancing Efficiency of Solar Heater Box with Linear Actuator for Maximizing Solarization - Agha Mushtaque Ahmed; Imran Khatri; Irfan Ahmed Halepoto; Masood Nazir Khoso (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
Worldwide, stored grain pests are massively infesting most stored crops and their by-products. The main losses are due to infestation of these pests occurring on various carriers just prior to harvest, during storage or shipping. Methyl bromide and phosphine fumigation have been widely used for phytosanitary treatment of stored grains but are recognized as highly effective in depleting ozone, and similarly, residue-free grains are important for thermal disinfection. Solarization is one of the best ways to manage and disinfect crops, the traditional solarization methods are already practised by farmers but are inefficient to kill all stages of pests and require additional land exposed to the sun. In this work, thermal disinfection systems using solar heaters are proposed, designed, and developed to offset the actual lethal heat window. For the experiment work, the solar heater boxes were constructed in an octagon shape with 135o at the base for trapping maximum heat inside the solar the heater box. The characteristics of the proposed system proved simpler, faster, and inexpensive but equally effective to achieve the desired results in terms of heat generation and seed moisture.